High-throughput phenotyping and improvements in breeding cassava for increased carotenoids in the roots - Belalcázar, John Eiver; Dufour, D.L.; Andersson, Meike S.; Pizarro, Mónica; Luna, Jorge; Londoño Hernandez, Luis Fernando; Morante, Nelson; Jaramillo Valencia, Angélica M.; Pino, Lizbeth; Becerra López Lavelle, Luis Augusto; Davrieux, Fabrice; Talsma, Elise F.; et al. (Wiley, 2016)
Past research developed reliable equations to base selections for high β-carotene on near-infrared spectroscopy (NIR) predictions (100 genotypes d−1) rather than with high-performance liquid chromatography (HPLC) (<10 samples d−1). During recent harvest, CIAT made selections based on NIR predictions for the first time. This innovation produced valuable information that will help other cassava (Manihot esculenta Crantz) breeding programs. A total of 284 samples were analyzed with NIR and HPLC for total β-carotene (TBC) and by the oven method for dry matter content (DMC). Results indicated that NIR reliably predicted TBC and DMC. In addition, 232 genotypes grown in preliminary yield trials (PYTs) were harvested at 8.5 and 10.5 mo after planting (one plant per genotype and age) and root quality traits analyzed (by NIR only). Repeatability of results at the two ages was excellent, suggesting reliable results from NIR. In contrast to previous reports, age of the plant did not influence carotenoids content in the roots. The availability of a high-throughput NIR protocol allowed comparing results (for the first time) from seedling and cloned plants from the same genotype. Results showed very little relationship for DMC between seedling and cloned plants (R2 = 0.09). There was a much better association for TBC (R2 = 0.48) between seedling and cloned plants. It is postulated that variation in the environmental conditions when seedling and cloned plants (from the same genotype) may be responsible for these weak associations. Important changes in selection strategies have been implemented to overcome problems related to a lengthy harvesting season.